Discrete element modelling of constant strain rate and creep tests on a graded asphalt mixture - Cai, Wei (2013)
This thesis investigates the use of Discrete Element Modelling (DEM) to simulate the elastic and viscoelastic deformation behaviour of an asphalt mixture. A numerical specimen preparation procedure has been developed to produce specimens with an isotropic stress and correct volumetrics. Stone mastic asphalt has been chosen in this project because of its high content of coarse aggregate and binder-rich mortar. A range of uniaxial compression tests have been undertaken in the laboratory under various loading speeds and stresses. The axial stress, axial strain and radial strain were recorded during the tests. The peak stress is found to be as a power-law function of the strain rates for the asphaltic material.